External iliac vein to inferior vena cava bypass as an alternative management for external iliac vein stenosis and thrombosis in renal transplant recipients - Hendarso, Muhammad Radityo (BMJ Publishing Group, 2022)
An man in his early 40s suffered from end-stage renal disease and underwent living donor renal transplantation. Doppler ultrasonography before surgery showed a normal iliac artery and vein without any thrombus. There was clear evidence of urine production intraoperatively. On the 5th postoperative day, there was no improvement in his renal function, and painless right leg oedema was noted. The clinical workup revealed pitting oedema without loss of arterial pulsation, discolouration or focal tenderness in the right leg. Serial Doppler ultrasonography examination showed thrombus progression from the right popliteal vein to the right external iliac vein around renal vein anastomosis despite anticoagulant administration with a downtrend of diuresis and worsening renal function. This condition led the patient to undergo surgical exploration on the 10th day post-transplantation. We decided to perform a thrombectomy and bypass the right external iliac vein to the inferior vena cava.